The containment of labour in accelerated global supply chains: the case of Piraeus Port. (1st July 2014) - ,; ,; ,
Abstract : This article presents a case study of the sale of two of the three piers at the formerly state-owned container port of Piraeus, in Greece to a Chinese company, COSCO, formng a crucial hub in the transit of goods to European markets, and examines the impacts on labour. It places this study in the context of the global consolidation, restructuring and acceleration of supply chains as well as in the specific context of privatisation of infrastructure and deregulation of labour in Greece in the aftermath of the debt crisis. Anatomising the tangled dynamics of deterritorialisation and reterritorialisation, it illustrates the complexity of the interrelationships between specific local factors and global forces in reshaping work. It also shows how the fragmentation of labour resulting from these impacts makes it easy for global corporations in the logistics sector both to consolidate their power and to evade contemporary forms of labour mobilisation. After chronicling the forms of resistance adopted by workers at the port, the article concludes by reflecting on the implications for organisation along the increasingly tightly integrated supply chains which link the labour of production workers with that of logistics workers.